2018
DOI: 10.1016/j.watres.2018.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of two biofiltration systems treating micropollutants from road runoff

Abstract: The treatment efficiency of a vegetative filter strip and a biofiltration swale treating heavily loaded road runoff are evaluated. Concentrations measured in water drained from the two systems are compared to those in untreated road runoff collected from a reference catchment for a wide range of contaminants including organic carbon, nutrients (N and P), trace metals, and organic micropollutants (polycyclic aromatic hydrocarbons (PAH), total petroleum hydrocarbons (TPH), alkylphenols, bisphenol-A, phthalates),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 43 publications
7
51
1
1
Order By: Relevance
“…Water sampling is detailed elsewhere [23]. Briefly, water was collected in proportion to flow volume in order to estimate event mean concentrations.…”
Section: Water Sampling and Pre-treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Water sampling is detailed elsewhere [23]. Briefly, water was collected in proportion to flow volume in order to estimate event mean concentrations.…”
Section: Water Sampling and Pre-treatmentmentioning
confidence: 99%
“…Water samples were collected within 24 h of each rain event and sent to partner laboratories within 24 h of collection where they are immediately filtered. Water was analysed for a large number of water quality parameters and micropollutants [23], which were analysed in the particulate and dissolved phases. The present work focuses on a subset of these parameters, chosen to represent the pollutants from different families and with varying properties: total suspended solids (TSS), organic carbon (OC), two trace metals (Cu and Zn), two PAHs (pyrene-Pyr and phenanthrene-Phen), bisphenol A (BPA), two alkylphenols (octylphenol-OP and nonylphenol-NP) and one phthalate (bis(2-ethylhexyl) phthalate-DEHP).…”
Section: Water Sampling and Pre-treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in France [48] showed that predominantly particulate pollutants, including Pb, Zn and polycyclic aromatic hydrocarbons, were very efficiently removed (90%) in a filter strip and a swale treating road runoff. On the other hand, lower removals were observed during the first months of operation and for total concentrations of moderately particulate micropollutants.…”
Section: Filter Strips and Vegetated Swalesmentioning
confidence: 99%